Matematyka
rafano
3

Oblicz : a) (-4)²+5²- [latex] 2^{0} [/latex] = b) -6²+( [latex] \frac{1}{3}[/latex] )²-2= c) (1 [latex] \frac{1}{3}[/latex])² - (1 [latex] \frac{1}{2}[/latex]) ³ =

+0
(1) Odpowiedź
Diana94

[latex](-4)^2+5^2-2^0=16+25-1=40[/latex] [latex]-6^2+(\frac{1}{3})^2-2=-36+\frac{1}{9}-2=-38+\frac{1}{9}=-37\frac{8}{9}[/latex] [latex](1\frac{1}{3})^2-(1\frac{1}{2})^3=(\frac{5}{3})^2-(\frac{3}{2})^3=\frac{25}{9}-\frac{27}{8}=\frac{200}{72}-\frac{243}{72}=-\frac{43}{72}[/latex]

Dodaj swoją odpowiedź